The role of visual awareness for conflict adaptation in the masked priming task: comparing block-wise adaptation with trial-by-trial adaptation - Hasegawa, Kunihiro; Takahashi, Shin’ya (Frontiers in Psychology, 2014)
This study investigated the role of participants’ visual awareness in the block-wise and the trial-by-trial adaptations. We employed a subliminal response compatibility task in which a prime arrow was briefly presented before the target arrow, and the participants were requested to indicate the direction of the target arrow. The direction of the prime and direction of the target were either the same (compatible trial) or different (incompatible trial). To examine block-wise adaptation, two blocks were conducted, i.e., the Neutral block (50% compatible and 50% incompatible trials) and the Incompatible block (10% compatible and 90% incompatible trials). The results showed the existence of the block-wise adaptation without participants’ visual awareness. The compatibility effect on both response time and error rate was smaller in the Incompatible block than in the Neutral block. Moreover, a separate data analysis based on the preceding trial type revealed that the trial-by-trial adaptation of cognitive control was observed only in the error rate. These results suggest the different role of visual awareness in the block-wise and trial-by-trial adaptations.